PENERAPAN ALGORITMA COSINE SIMILARITY UNTUK MENGIDENTIFIKASI KEBUTUHAN BELAJAR MURID DI SEKOLAH BERBASIS DATA ANALISIS - Aruni Muprida; Azrai Sirait (Smart Education, 2025)
Abstract: In an educational context, Cosine Similarity can be used to compare students' learning profiles, for example based on exam results, assignments, or material preferences, to determine the level of similarity between them. The results of this calculation can help teachers design more personalized learning programs, such as providing additional material for students who are struggling or special challenges for students who have already mastered the material well. The data used in this study were learning outcomes, grades, interests, and academic activities. The purpose of this study was to implement the Cosine Similarity algorithm to identify students' learning needs. The test results for four students can be seen in Andi's final score of 0.932. The highest profile: